"Los míos... ¡todos asustados!": Vulnerabilidad infantil y trayectorias de desarrollo en los Valles Calchaquíes salteños - Remorini, Carolina (2016)
This work analyzes the narrative of women of different generations in which fright - as a vernacular category - emerges as the cause of numerous health problems that take place along the life trajectory of mothers as well as their children, having a vital impact on child development. This narrative was obtained in the framework of an ethnographic research in Molinos (Calchaquí Valleys, Salta). We analyzed the way in which the interviewees present the sequences of events surrounding the emergence of their own episodes of illness and those of their children. We also recognized actors, resources and relationships involved. We analyzed references to episodes of fright and its variants, which -of the absence of timely diagnosis and treatment - can cause problems of different severity on health and child development. In the framework of their narrative, the appeal to nosological categories of traditional medicine is justified in those cases whose resolution involves numerous therapeutic instances or due to the inefficiency of other alternatives. Thus, in the process of finding effective options for the resolution of a health problem, these categories are integrated into new hypotheses that reorient the action.